ANALISIS DAMPAK EKONOMI TERHADAP PERILAKU MASYARAKAT PERKOTAAN DI MASA PANDEMI COVID-19 - Khusnul Khotimah (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi (JEBMA), 2021)
Coronavirus disease 2019 (COVID-19) is a virus that is spreading rapidly and widely around the world. This virus originated in China which is the city of Wuhan in December 2019. Within a few months, the virus has spread to all parts of the world, and Indonesia is one of the countries affected by this virus. In Indonesia, Covid-19 was confirmed in March 2020. With the Covid-19 virus, it caused many impacts in various sectors, ranging from the economic sector, health, education and many other sectors that were affected by the Covid-19. Likewise in the economic sector, it has an impact on the behavior of the people of Pasuruan City. This study aims to determine the economic impact on the behavior of urban communities during the Covid-19 pandemic in Pasuruan City. The research method uses descriptive qualitative methods. The research instrument used interview guides, and recording tools used during interviews, books, and stationery. The data from the interviews were analyzed according to the themes found. The research results obtained include the economic impact on people's behavior, the level of public consumption, and factors that influence people's behavior during the Covid-19 pandemic in Pasuruan City.